Pemberdayaan UMKM Sabila Snack & Bakery Melalui Penguatan Manajemen Usaha dan Administrasi Keuangan - Arfan Maulana; Karina Reda Setyorini; Mukharomah Nur Achiroh; Tea Martina Laores; Syifa Aulia Sari; Dhea Pranandasari; Valentina Alfi Maulia; Galeh Pangestu; Fudji Sri Mar'ati (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
Culinary MSMEs serve as a vital economic pillar; however, they often encounter significant internal management obstacles and low digital competitiveness. Sabila Snack & Bakery faces complex challenges, including unstructured production schedules, limited digital marketing literacy, inconsistent visual branding, and financial record-keeping that remains intertwined with personal funds. This community service initiative aims to provide applicable solutions by strengthening internal management and digital marketing strategies to enhance operational efficiency and business competitiveness. The methodology employed is Participatory Action Research (PAR), encompassing stages of observation, interviews, technical assistance, and evaluation. The results indicate a significant transformation in business governance. The implementation of daily production schedules has successfully improved workflow regularity and operational efficiency. Furthermore, branding reinforcement through the establishment of a permanent logo, the creation of systematic product catalogs, and the optimization of social media platforms such as WhatsApp Business, Instagram, and TikTok has effectively increased business visibility and professionalism in the digital sphere. Additionally, the application of a simple bookkeeping system has fostered administrative discipline and a clear separation between personal finances and business capital. Overall, this intervention has successfully transitioned the business from traditional management patterns toward a more structured, professional, and sustainable management model ready to compete in a broader market.